The development of multibeam quarter-cut radial line slot array (RLSA) antennas - Purnamirza, Teddy; Yusma, Muhammad Reynaldi; Shardarbekovich, Junisbekov M.; Batyrbekovich, Kabanbayev A.; Mohd Ibrahim, Imran; Rahmi, Depriwana (Electromagnetics Academy, 2024)
This research aimed to introduce multibeam quarter-cut Radial Line Slot Array (RLSA) antennas for the first time. These antennas are distinct from the multibeam full-circle RLSA due to the use of quarter RLSA, making it suitable for small devices. To achieve beams directed to the backside, an unconventional approach was taken by placing slots on the antenna’s background. A technique comprising the deletion of specific slot pairs in the radiating element was introduced to balance the gain and beam shape. Furthermore, thirty-six multibeam quarter RLSA models were designed and simulated. The best model was then fabricated and measured to validate the simulation results. Consequently, the results showed the possibility of designing multibeam antennas with symmetrical beams in terms of gain, direction, and beamwidth, which were 6.23 dBi, 37◦ , 145◦ , and 34◦, respectively. The gain of 6.23 dBi was 3 dB less than the single-beam antennas, consistent with the theory of beam splitting. Additionally, antennas exhibited low reflection and a broad bandwidth suitable for Wi-Fi needs. Finally, the agreement between measurement and simulation validated the design of antennas.